2015
DOI: 10.1128/jb.00603-15
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Timing: Contrasting Effects of Hydrogen Sulfide on Oxidative Stress Response in Shewanella oneidensis

Abstract: Hydrogen sulfide (H 2 S), well known for its toxic properties, has recently become a research focus in bacteria, in part because it has been found to prevent oxidative stress caused by treatment with some antibiotics. H 2 S has the ability to scavenge reactive oxygen species (ROS), thus preventing oxidative stress, but it is also toxic, leading to conflicting reports of its effects in different organisms. Here, with Shewanella oneidensis as a model, we report that the effects of H 2 S on the response to oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Thiol compounds bind with substantial avidity to soft metals and hemes and therefore are potentially inhibitory to enzymes that use these cofactors (Nies, 2003, Wu et al, 2015, Vitvitsky et al, 2015, Bolic et al, 2015, Nagy, 2015). Zinc has a moderate affinity for thiols, and zinc enzymes can be inhibited when moderate concentrations of cysteine or sulfide coordinate and perhaps extract the metal (Martin & Maricle, 2015, Gu & Imlay, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thiol compounds bind with substantial avidity to soft metals and hemes and therefore are potentially inhibitory to enzymes that use these cofactors (Nies, 2003, Wu et al, 2015, Vitvitsky et al, 2015, Bolic et al, 2015, Nagy, 2015). Zinc has a moderate affinity for thiols, and zinc enzymes can be inhibited when moderate concentrations of cysteine or sulfide coordinate and perhaps extract the metal (Martin & Maricle, 2015, Gu & Imlay, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Such changes were observed among fish that live in sulfidic waters and plants that must tolerate sulfide exudations from sediments during flooding. Intriguingly, a cytochrome c oxidase in a sulfate-reducing bacterium appeared to be tolerant of 0.25 mM sulfide, but the structural basis was not explored (Wu et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that H 2 S elicited microbicidal effects by inhibiting the activities of superoxide dismutase and catalase (10,27). In addition, high levels of sulfide impose survival stress on Desulfovibrio vulgaris by sequestering essential trace metals (28).…”
Section: Fig 3 Effects Of H 2 S On Intracellular Sulfide Levels and Gmentioning
confidence: 99%
“…The latter function of H 2 S seems to be universal, because it has been implicated in bacterial defense against reactive oxygen species (ROS) and antibiotics-induced oxidative damage (2). H 2 S can also kill microorganisms by inhibiting antioxidant enzymes during induced oxidative stress (3,4). These seemingly contradictory attributes of H 2 S highlight its concentration-dependent dual nature: at high concentration, it is a toxic gas, and at lower physiological concentrations, it is a signaling and/or protective molecule.…”
mentioning
confidence: 99%